2020
DOI: 10.48550/arxiv.2010.01044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multilevel quasi-Monte Carlo for random elliptic eigenvalue problems I: Regularity and error analysis

Abstract: Random eigenvalue problems are useful models for quantifying the uncertainty in several applications from the physical sciences and engineering, e.g., structural vibration analysis, the criticality of a nuclear reactor or photonic crystal structures. In this paper we present a simple multilevel quasi-Monte Carlo (MLQMC) method for approximating the expectation of the minimal eigenvalue of an elliptic eigenvalue problem with coefficients that are given as a series expansion of countably-many stochastic paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 33 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…Note that similar results also hold for general N , but with N replaced by the Euler Totient function, which counts the number of integers less than and coprime to N , see, e.g., [13,Theorem 5.10]. For more details on the general theory of lattice rules see [13], and for a theoretical analysis of randomly shifted lattice rules for MLQMC applied to (1.1) see [21].…”
Section: Quasi-monte Carlo Integrationmentioning
confidence: 84%
See 4 more Smart Citations
“…Note that similar results also hold for general N , but with N replaced by the Euler Totient function, which counts the number of integers less than and coprime to N , see, e.g., [13,Theorem 5.10]. For more details on the general theory of lattice rules see [13], and for a theoretical analysis of randomly shifted lattice rules for MLQMC applied to (1.1) see [21].…”
Section: Quasi-monte Carlo Integrationmentioning
confidence: 84%
“…In the companion paper [21], it is shown that for h sufficiently small 1 the spectral gap of the FE eigenvalue problem (2.11) satisfies the uniform lower bound…”
Section: Finite Element Methods For Eigenvalue Problemsmentioning
confidence: 99%
See 3 more Smart Citations